Positive Reinforcement: an Approach to Enhancing Accountability and Drive among Students (MultiTech Publisher, 2023)
The Positive reinforcement plays a prominent role in several educational institutions and individual classrooms around the world. Providing commendation and incentives to students who exhibit good behaviors and fulfill academic responsibilities within the classroom setting enables educators to direct their attention towards desired behaviors while minimizing emphasis on undesirable conduct that may arise. This study aims to explain the perspectives, positive reinforcement is believed to foster a heightened feeling of accountability among students, hence motivating them to exert more effort in order to accomplish tasks. This paper attributed to the anticipation of obtaining commendation or a tangible incentive as a result of their efforts. There are other viewpoints positing that the use of positive reinforcement, such as praise and awards, may result in a decline in intrinsic motivation, an increased disparity between educators and learners, and a reduction in performance levels. Critics contend that an abundance of praise and the provision of rewards for exhibiting good actions just elicit short-term conformity, rather than cultivating a lasting feeling of accountability and drive among pupils. The discourse pertaining to positive reinforcement remains a subject of contention within the field of education